Horizontal distribution of rotifers in a subtropical shallow lake (Paraná floodplain, Argentina) - Jose, Susana Beatriz (2012)
In water bodies where cladocerans are typically small or present in low biomass, such as in the tropics and subtropics of South America, rotifers may play a larger role in ecosystem functioning than in temperate lakes. The aim of this study was to analyze the horizontal distribution of richness and abundance of rotifers, their diel distribution patterns, and the relative importance of physical and biotic characteristics as their shaping factors, in a subtropical shallow vegetated lake of the Paraná River floodplain (Argentina). Three sampling stations were located along the major axis of the lake, one in open waters and two in littoral area dominated by the emergent Panicum elephantipes, Cyperus alternifolius and floating mats of the filamentous algae Cladophora spp. Two further stations were located on the transverse axis. Rotifer samples were taken on four occasions (at noon and midnight) during a five week period in the summer to avoid possible changes in the pattern of distribution of macrophytes and hydrological variability of the lake. Rotifer richness was higher in the littoral zone whereas rotifer abundance was higher in the limnetic zone. Some rotifers, such as Brachionus havanaensis and Keratella tropica exhibited changes in their diel horizontal distribution with higher concentrations of organisms at vegetated zones during the day time. In contrast, Polyarthra sp. were more abundant at night-time in both limnetic and littoral areas. The heterogeneous horizontal distribution of rotifers cannot be explained by the rather homogeneous distribution of both physical environmental factors and phytoplankton abundance. Rotifer distribution may be related to a complex of factors including the presence or absence of vegetation, the relatively uniform distribution of visual predators (fishes) and the heterogeneous distribution of non-visual predators (insects and shrimps).